Effect of Total Suspension on Macrozoobenthos in the Aek Pala River - Fahrur Rozy Siregar; Arman Harahap (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Aek Pala River is a water used by the surrounding community for various activities. In addition to fishing activities by the local community, the Aek Pala river is also a natural tourist spot that causes turbidity from suspended solids. This situation affects biodiversity, especially macrozooebenthos in these waters. Macrozooebenthos is a group of animals that live on the bottom of the waters and are often found living in association with other organisms. This study aims to determineeffect of total suspended solids on macrozoobenthos in the Aek Pala river. The sampling technique in this study used a purposive random sampling technique, while the research used a descriptive method. The results showed that the total suspended solids content in the waters of the Aek Pala . riverranged from 105.20 mg/l -135.15 mg/l. The largest value was found at station IV amounting to 135.15 mg/l, while the lowest value was at station II amounting to 105.20 mg/l. There are 5 types of macrozoobenthos found in the Aek Pala river, namely zooplankton, bivalves, annelids, crustaceans and gastropods. The results of the calculation of the community structure of various types of macrozooebenthos were found in the form of calculation results, namely the highest diversity index (H') was at station III amounting to 0.7035, the highest uniformity index (e) was at station III amounting to 0.437, dominance index (C ) is the highest at station I amounting to 0.766, andrelative abundance index (KR),the highest is at station I amounting to31,650.